Socioeconomic Disparities in Completed Antenatal Care: Evidence from Nigeria - Nikmatur Rohmah; Agung Dwi Laksono; Abubakar Yakubu Abbani; Ratu Matahari; Yuli Astuti; Ratna Dwi Wulandari (JURNAL INFO KESEHATAN, 2025)
The Maternal Mortality Rate is still high in Nigeria. Complete antenatal care (ANC) of eight visits during pregnancy is an important strategy to control this condition. This research analyzed the socioeconomic disparities in completed ANC in Nigeria. The study examined secondary data from the 2018 Nigerian Demographic and Health Survey. The study included 21,792 women aged 15 to 49 who had given birth in the previous five years. We looked at eight control factors in addition to completed ANC as an outcome variable and socioeconomic as an exposure variable: domicile, age, religion, marital status, education, occupation, and parity. Data were analyzed using binary logistic regression. The result showed the completed ANC proportion in Nigeria is 21.6%. Meanwhile, the poorer were 1.316 times more likely than the poorest to perform completed ANC (AOR 1.316; 95% CI 1.316-1.317). The middle was 1.994 times more likely to achieve completed ANC than the poorest (AOR 1.994; 95% CI 1.993-1.994). Meanwhile, the richer were 2.808 times more likely than the poorest to achieve completed ANC (AOR 2.808; 95% CI 2.807-2.808). Moreover, the richest were 4.112 times more likely to perform completed ANC than the poorest in Nigeria (AOR 4.112; 95% CI 4.112-4.113). The study revealed significant socioeconomic disparities in the completion of ANC in Nigeria, with wealthier women being more likely to achieve completed ANC compared to their less-wealthy counterparts.